Effect of Azobacter sp. and N Fertilizer on the Growth of Oil Palm Seedling Inoculated with Ganoderma sp - Happy Widiastuti (International Journal of Oil Palm, 2018)
Excess application of nitrogen fertilizer causes soil nutrient imbalances and reduce the number and soil microbial diversity. This condition could induce soil born dieseses such basal stem rot caused by Ganoderma sp. A study was conducted to enhance the plant tolerance to Ganoderma sp. through introduction of microbial community especially non-symbiotic N fxing bacteria, Azotobacter sp. Plant materials used were 4 months old of germinated oil palms, while Ganoderma sp. was isolated from Bekri, Lampung. There are seven treatments tested i e Azotobacter sp. + Ganoderma sp. (+A+G), Azotobacter sp. + 30% N fertilizer of recommended dosage + Ganoderma sp. (+A+30N+G), Azotobacter sp. + 60% N fertilizer of recommended dosage + Ganoderma sp. (+A+60N+G), Azotobacter sp. + 100% N fertilizer of recommended dosage + Ganoderma sp. (+A+100N+G), 100% N fertilizer of recommended dosage + Ganoderma sp. (+100N+G), Ganoderma sp. inoculation (positive control, +G), and non-inoculated Ganoderma sp. (negative control, -G). The result showed that Azotobacter sp.enhanced the height of plant inoculated with Ganoderma sp. when accompanied with N fertilizer of 30 to 100% of recommended dose. Moreover, +A+100N+G seedling had signifcantly higher fresh and dry weight of shoot compared to those of +G seedling or +100N+G seedling